A kind of ultrafine grinding medium of rutile titanium dioxide powder and preparation method thereof
By using ultra-fine grinding media of rutile-type titanium dioxide powder composed of modified mica and other components, the problems of insufficient hardness and high cost of existing grinding media are solved, and high hardness, low cost and colorless pollution are achieved. Grinding effect.
Patent Information
- Application Number
- CN202411398751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing grinding media has problems of insufficient hardness and high cost when grinding titanium dioxide powder, and the powder color contamination caused by wear of abrasives.
Utilizes the ultra-fine grinding medium of rutile-type titanium dioxide powder composed of magnesium oxide, alumina, kaolin, Hengyang mud, modified mica, feldspar and nanotitanium dioxide pigments, and is fired through ball milling, stirring, ball forming and kiln. Prepare it in steps such as preparation, and the modified mica is obtained by pretreatment of hydrochloric acid and ammonium bicarbonate solution and reacting with sodium silicate solution.
It improves the hardness and wear resistance of the abrasive media, reduces production costs, and prevents powder color pollution caused by abrasive wear, and the crushing strength reaches 950N.
Abstract
Description
Technical Field
[0001] The invention relates to the field of grinding media, and in particular to a rutile titanium dioxide powder ultrafine grinding medium and a preparation method thereof. Background Art
[0002] Rutile titanium dioxide is widely used in plastics, inks, white pigments and metal topcoats for luxury cars due to its excellent thermal stability, chemical stability, weather resistance and high refractive index. As a new type of inorganic functional material, titanium dioxide nanopowder has a particle size of only 1.5 times that of ordinary TiO 2 The diameter of the rutile titanium dioxide is about one tenth of that of the ore, mostly 10 to 50 nm, and has very valuable optical properties. The main equipment used in the wet grinding process of rutile titanium dioxide is sand mill, ball mill, colloid mill, etc., and the grinding medium is the medium for energy transfer between the mill and the mineral. During the working process of the mill, the medium mainly crushes the mineral in four ways: extrusion, shearing, scrubbing and impact.
[0003] Chinese patent CN101921101A discloses the production process of zirconium-aluminum composite ceramic beads. The product composition includes 3-6 parts of zirconium silicate, α-Al 2 O 3 3-10 parts, feldspar 1-3 parts, calcined kaolin 1-3 parts and mullite powder 1-3 parts. The strength of this grinding medium is relatively low, and the hardness is generally only 130-150MPa. Titanium dioxide pigments are hard and have great abrasion. The worn abrasives affect the color of the grinding object (such as white titanium dioxide pigments), so it is not suitable for grinding. In addition, due to the relatively high price of zirconium, the cost of this ceramic grinding medium is high and it is difficult to promote it in large quantities.
[0004] Chinese patent CN104004497A discloses an ultrafine grinding medium for red iron oxide powder. The product ingredients include alumina, kaolin, Suzhou clay, potassium feldspar, quartz powder, zirconium oxide and nano red iron oxide pigment. Also, due to the relatively high price of zirconium, the manufacturing cost of the product is high and it does not have a market advantage.
[0005] Therefore, it is particularly important to develop a high-performance grinding medium with high hardness and low cost. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide an ultrafine grinding medium for rutile titanium dioxide powder and a preparation method thereof. The present invention can improve product strength, reduce production costs, and prevent the color of titanium dioxide powder from being contaminated by abrasive wear.
[0007] The specific technical solutions of the present invention are as follows:
[0008] In order to achieve the above object, the present invention adopts the following technical scheme: a rutile titanium dioxide powder ultrafine grinding medium, comprising the following components in parts by weight:
[0009] 20-25 parts of magnesium oxide, 10-15 parts of aluminum oxide, 20-25 parts of kaolin, 10-20 parts of Hengyang mud, 5-15 parts of modified muscovite, 1-3 parts of feldspar and 5-10 parts of nano titanium dioxide pigment.
[0010] A method for preparing ultrafine grinding media of rutile titanium dioxide powder specifically comprises the following steps:
[0011] S1: adding magnesium oxide, aluminum oxide, kaolin, Hengyang mud, modified muscovite, feldspar and nano titanium dioxide pigment into a ball mill, and grinding to 1700-2000 mesh, and then discharging the material to obtain mixed raw material ultrafine powder;
[0012] S2: Stir and disperse the mixed raw materials at a speed of 1000-1500 r / min for 0.5-1 h, then put them into a spheroidizer and roll them into spheres with a diameter of 5 mm-30 mm;
[0013] S3: Firing in a kiln at a heating rate of 5-10°C / min, from room temperature to 600-800°C, keeping the temperature constant for 2-3h, and then firing at a heating rate of 3-6°C / min, and when the temperature reaches 1000-1200°C, keep the temperature for 0.5-1h;
[0014] S4: Natural cooling and annealing, taking out of the kiln, self-polishing the sphere, and screening to obtain the finished product.
[0015] Preferably, the preparation method of modified muscovite comprises the following steps:
[0016] 1) Place muscovite in a hydrochloric acid solution at 80-100°C and stir continuously for 2-3 hours, then rinse with clean water, filter and dry, and crush to 500-800 mesh to obtain mica material;
[0017] 2) Add the mica material to the ammonium bicarbonate solution, and heat it in a water bath at 50-60°C for 3-5 minutes to obtain a pre-treated mixed solution;
[0018] 3) The pretreated mixed solution is filtered under reduced pressure, and dried and calcined at a temperature of 150 to 200° C. for 1 to 2 hours to obtain pretreated muscovite powder;
[0019] 4) Mix the muscovite powder with 40% to 50% sodium silicate solution by weight, disperse it by ultrasonic for 30 to 60 minutes, and then heat it to 800 to 1000°C at a rate of 3 to 4°C / min and keep it warm for 30 to 60 minutes;
[0020] 5) After natural cooling, vacuum filtration, washing, drying, grinding with a mortar, and sieving to obtain modified muscovite.
[0021] Use hydrochloric acid and ammonium bicarbonate solution to remove impurities and ions on the surface of muscovite, and change its surface properties to increase reaction sites and increase its reactivity with other substances. Add sodium silicate solution to muscovite and heat it rapidly to make sodium silicate and muscovite tightly combined, and the aluminum ions in muscovite are exchanged, dissolved and reorganized with some ions in sodium silicate solution to obtain modified muscovite containing aluminum silicate layered structure. Since sodium silicate is a weak acid salt, it is very easy to hydrolyze under high temperature heating conditions. In order to reduce the loss of sodium silicate and promote the reaction between muscovite and sodium silicate solution, sodium hydroxide solution is added to the sodium silicate solution added in step 4), and the pH is adjusted to 7.5-8.5 to inhibit the hydrolysis of sodium silicate, increase the conversion rate of the reaction between sodium silicate and muscovite, and thus improve the fineness and smoothness of muscovite. Then magnesium oxide, aluminum oxide, kaolin, Hengyang mud, feldspar, nano titanium dioxide pigment and modified muscovite are fired at high temperature. The modified muscovite increases the density and compactness of the product, thereby improving the hardness, strength and wear resistance of the product.
[0022] Preferably, the concentration of the hydrochloric acid solution in step 1) is 5% to 10%.
[0023] Preferably, the concentration of the sodium bicarbonate solution in step 2) is 10% to 20%.
[0024] Preferably, the concentration of the sodium silicate solution in step 4) is 2% to 5%.
[0025] The beneficial effects of the present invention are:
[0026] The present invention proposes a rutile titanium dioxide powder ultrafine grinding medium and a preparation method thereof. Muscovite is pretreated with hydrochloric acid and ammonium bicarbonate solution, and then a sodium silicate solution with a pH value of 7.5 to 8.5 is added to the muscovite, and the mixture is rapidly heated. The aluminum ions in the muscovite are exchanged, dissolved and reorganized with part of the ions in the sodium silicate solution to obtain a modified muscovite containing an aluminum silicate layered structure. The modified muscovite can significantly improve the hardness, strength and wear resistance of the muscovite, thereby improving the hardness and wear resistance of the product, and the maximum crushing strength can reach 950N. Moreover, the final product is white in color, which can effectively prevent the color of the titanium dioxide powder from being contaminated by abrasive wear products. The process of the present invention is simple to operate, stable and reliable in operation, and low in cost. DETAILED DESCRIPTION
[0027] The technical scheme of the present invention is further described below through specific examples. Unless otherwise specified in the present invention, the raw materials and equipment used can be purchased from the market or are commonly used in the art, and the methods in the embodiments are conventional methods in the art unless otherwise specified.
[0028] Example 1
[0029] A rutile titanium dioxide powder ultrafine grinding medium is prepared from the following raw materials in parts by weight: 20 parts of magnesium oxide, 10 parts of aluminum oxide, 20 parts of kaolin, 10 parts of Hengyang mud, 5 parts of modified muscovite, 1 part of feldspar and 5 parts of nano titanium dioxide pigment.
[0030] The preparation method of modified muscovite comprises the following steps:
[0031] 1) Place muscovite in a 5% hydrochloric acid solution at 80°C and stir for 2 hours, then rinse with clean water, filter and dry, and crush to 500 mesh to obtain mica material;
[0032] 2) Add the mica material to a 10% ammonium bicarbonate solution, heat it in a water bath at 50°C for 3 minutes to obtain a pre-treated mixed solution;
[0033] 3) The pretreated mixed solution was filtered under reduced pressure, and dried and calcined at 150° C. for 1 h to obtain pretreated muscovite powder;
[0034] 4) Adjust the pH of the 2% sodium silicate solution to 8.5 with sodium hydroxide solution, then mix the muscovite powder with 40% sodium silicate solution by mass, disperse it by ultrasonic for 30 minutes, and then heat it to 800°C at a rate of 3°C / min and keep it warm for 30 minutes;
[0035] 5) After natural cooling, vacuum filtration, washing, drying, grinding with a mortar, and sieving to obtain modified muscovite.
[0036] A method for preparing ultrafine grinding media of rutile titanium dioxide powder specifically comprises the following steps:
[0037] S1: adding magnesium oxide, aluminum oxide, kaolin, Hengyang mud, modified muscovite, feldspar and nano titanium dioxide pigment into a ball mill, and after ball milling to 1700 mesh, discharging the material to obtain ultrafine powder of mixed raw materials;
[0038] S2: The mixed raw materials were stirred and dispersed at a speed of 1000 r / min for 0.5 h, and then put into a spheroidizer and rolled to form spheres with a diameter of 5 mm;
[0039] S3: Firing in a kiln at a heating rate of 5°C / min, from room temperature to 600°C, keeping the temperature constant for 2h, and then firing at a heating rate of 3°C / min, and when the temperature reaches 1000°C, keep the temperature constant for 0.5h;
[0040] S4: Natural cooling and annealing, taking out of the kiln, self-polishing the sphere, and screening to obtain the finished product.
[0041] Example 2
[0042] A rutile titanium dioxide powder ultrafine grinding medium is prepared from the following raw materials in parts by weight: 25 parts of magnesium oxide, 15 parts of aluminum oxide, 25 parts of kaolin, 20 parts of Hengyang mud, 15 parts of modified muscovite, 3 parts of feldspar and 10 parts of nano titanium dioxide pigment.
[0043] The preparation method of modified muscovite comprises the following steps:
[0044] 1) Place muscovite in a 10% hydrochloric acid solution at 100°C and stir for 3 hours, then rinse with clean water, filter and dry, and crush to 800 mesh to obtain mica material;
[0045] 2) Add the mica material to a 20% ammonium bicarbonate solution, heat it in a water bath at 60°C for 5 minutes, and obtain a pre-treated mixed solution;
[0046] 3) The pretreated mixed solution was filtered under reduced pressure, and dried and calcined at 200° C. for 2 h to obtain pretreated muscovite powder;
[0047] 4) adjusting the pH of a 5% sodium silicate solution to 7.5 with a sodium hydroxide solution, then mixing the muscovite powder with a 40% sodium silicate solution by mass, ultrasonically dispersing for 60 minutes, and then heating to 1000°C at a rate of 4°C / min and keeping the temperature for 60 minutes;
[0048] 5) After natural cooling, vacuum filtration, washing, drying, grinding with a mortar, and sieving to obtain modified muscovite.
[0049] A method for preparing ultrafine grinding media of rutile titanium dioxide powder specifically comprises the following steps:
[0050] S1: adding magnesium oxide, aluminum oxide, kaolin, Hengyang mud, modified muscovite, feldspar and nano titanium dioxide pigment into a ball mill, and after ball milling to 2000 mesh, discharging the material to obtain ultrafine powder of mixed raw materials;
[0051] S2: The mixed raw materials were stirred and dispersed at a speed of 1500 r / min for 1 h, and then put into a spheroidizer and rolled into spheres with a diameter of 30 mm;
[0052] S3: Firing in a kiln at a heating rate of 10°C / min from room temperature to 800°C, keeping the temperature constant for 3h, and then firing at a heating rate of 6°C / min. When the temperature reaches 1200°C, keep the temperature constant for 1h;
[0053] S4: Natural cooling and annealing, taking out of the kiln, self-polishing the sphere, and screening to obtain the finished product.
[0054] Example 3
[0055] A rutile titanium dioxide powder ultrafine grinding medium is prepared from the following raw materials in parts by weight: 22 parts of magnesium oxide, 13 parts of aluminum oxide, 22 parts of kaolin, 15 parts of Hengyang mud, 10 parts of modified muscovite, 2 parts of feldspar and 8 parts of nano titanium dioxide pigment.
[0056] The preparation method of modified muscovite comprises the following steps:
[0057] 1) Place muscovite in 8% hydrochloric acid solution at 90°C and stir for 2.5 hours, then rinse with clean water, filter and dry, and crush to 650 mesh to obtain mica material;
[0058] 2) Add the mica material to a 15% ammonium bicarbonate solution, heat it in a water bath at 55°C for 4 minutes, and obtain a pre-treated mixed solution;
[0059] 3) The pretreated mixed solution was filtered under reduced pressure, and dried and calcined at 180° C. for 1.5 h to obtain pretreated muscovite powder;
[0060] 4) Adjust the pH of the 3.5% sodium silicate solution to 8.0 with sodium hydroxide solution, then mix the muscovite powder with the 45% sodium silicate solution, disperse it by ultrasonic for 45 minutes, and then heat it to 900°C at a rate of 3.5°C / min and keep it warm for 45 minutes;
[0061] 5) After natural cooling, vacuum filtration, washing, drying, grinding with a mortar, and sieving to obtain modified muscovite.
[0062] A method for preparing ultrafine grinding media of rutile titanium dioxide powder specifically comprises the following steps:
[0063] S1: adding magnesium oxide, aluminum oxide, kaolin, Hengyang mud, modified muscovite, feldspar and nano titanium dioxide pigment into a ball mill, grinding to 1850 mesh, discharging the material, and obtaining mixed raw material ultrafine powder;
[0064] S2: The mixed raw materials were stirred and dispersed at a speed of 1250 r / min for 0.75 h, and then put into a spheroidizer and rolled into spheres with a diameter of 15 mm;
[0065] S3: Firing in a kiln at a heating rate of 8°C / min from room temperature to 700°C, keeping the temperature constant for 2.5 hours, and then firing at a heating rate of 5°C / min. When the temperature reaches 1100°C, keep the temperature constant for 0.75h.
[0066] S4: Natural cooling and annealing, taking out of the kiln, self-polishing the sphere, and screening to obtain the finished product.
[0067] Comparative Example 1:
[0068] The difference between Comparative Example 1 and Example 3 is that the muscovite mica has not been modified.
[0069] Comparative Example 2
[0070] The difference between Comparative Example 2 and Example 3 is that the muscovite was not pretreated with hydrochloric acid and ammonium bicarbonate during modification.
[0071] Comparative Example 3
[0072] The difference between Comparative Example 3 and Example 3 is that the muscovite was not pretreated with ammonium bicarbonate during modification.
[0073] Comparative Example 4
[0074] The difference between Comparative Example 4 and Example 3 is that when the muscovite is modified, the pH of the sodium silicate solution is not adjusted to 7.5-8.5.
[0075] Test results:
[0076] Table 1 Product hardness and color results
[0077] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Crushing strength / N 880 950 860 360 430 380 500 color White White White White White White White
[0078] As can be seen from Table 1, the experimental examples and comparative examples are both white, which can effectively prevent the color of titanium dioxide powder from being contaminated by abrasive wear. The crushing strength of the example product is greater than that of the comparative example, which is mainly because the examples all contain modified muscovite, which can significantly improve the hardness, strength and wear resistance of muscovite, thereby improving the hardness and wear resistance of the product. Moreover, the pretreatment in the modification process of muscovite is also crucial. The hydrochloric acid and ammonium bicarbonate solution can not only remove impurities and ions on its surface, but also change its surface properties and increase reaction sites through the coordination of hydrochloric acid and ammonium bicarbonate. The crushing strength of the comparative example 3 product is close to that of the comparative example 1, indicating that in the pretreatment of the coordination of hydrochloric acid and ammonium bicarbonate, the effect is greatly reduced without ammonium bicarbonate. At the same time, during the modification process, the pH value of the sodium silicate solution is adjusted to 7.5-8.5 by dripping sodium hydroxide solution, which can effectively inhibit the hydrolysis of sodium silicate, reduce the loss of sodium silicate, promote the reaction of muscovite and sodium silicate solution, and improve the conversion rate of the reaction, thereby obtaining modified muscovite containing an aluminum silicate layered structure, thereby improving the hardness, strength and wear resistance of the product.
Claims
1. A rutile titanium dioxide powder ultrafine grinding medium, characterized in that: The invention comprises the following components by weight: 20-25 parts of magnesium oxide, 10-15 parts of aluminum oxide, 20-25 parts of kaolin, 10-20 parts of Hengyang mud, 5-15 parts of modified muscovite, 1-3 parts of feldspar and 5-10 parts of nano titanium dioxide pigment; The preparation method of the modified muscovite comprises the following steps: 1) placing muscovite in a hydrochloric acid solution at 80-100° C. and stirring continuously for 2-3 hours, then rinsing with clean water, filtering and drying, and crushing to 500-800 mesh to obtain mica material; 2) adding ammonium bicarbonate solution to the mica material, standing and heating in a water bath at 50-60° C. for 3-5 minutes to obtain a pre-treated mixed solution; 3) filtering the pre-treated mixed solution under reduced pressure, drying and roasting at a temperature of 150-200° C. for 1-2 hours to obtain pre-treated muscovite powder; 4) adjusting the pH of the sodium silicate solution to 7.5-8.5 with a sodium hydroxide solution, then mixing the muscovite powder with a sodium silicate solution of 40%-50% by mass, ultrasonically dispersing for 30-60 minutes, and then heating to 800-1000° C. at a speed of 3-4° C. / min, and keeping the temperature for 30-60 minutes; 5) after natural cooling, filtering under reduced pressure, washing, drying, and grinding with a mortar; The modified muscovite is ground and sieved to obtain the modified muscovite; the method for preparing the ultrafine grinding medium of the rutile titanium dioxide powder comprises the following steps: S1: adding magnesium oxide, aluminum oxide, kaolin, Hengyang mud, modified muscovite, feldspar and nano titanium dioxide pigment into a ball mill, ball-milling to 1700-2000 mesh, discharging the material, and obtaining the ultrafine powder of the mixed raw material; S2: stirring and dispersing the mixed raw material at a speed of 1000-1500 r / min; .5~1h, then put it into a ball forming machine and roll it into a sphere with a diameter of 5mm~30mm; S3: Firing in a kiln, the heating rate is 5~10℃ / min, from room temperature to 600~800℃, keep the temperature constant for 2~3h, and then fire at a heating rate of 3~6℃ / min. When the temperature reaches 1000~1200℃, keep it warm for 0.5~1h; S4: Natural cooling and annealing, take out of the kiln, polish the sphere by self-grinding, and screen out the finished product.
2. The ultrafine grinding medium for rutile titanium dioxide powder according to claim 1, characterized in that: The percentage concentration of the hydrochloric acid solution in step 1) is 5% to 10%.
3. The ultrafine grinding medium for rutile titanium dioxide powder according to claim 1, characterized in that: The percentage concentration of the ammonium bicarbonate solution in step 2) is 10% to 20%.
4. The ultrafine grinding medium for rutile titanium dioxide powder according to claim 1, characterized in that: The percentage concentration of the sodium silicate solution in step 4) is 2% to 5%.
Citation Information
Patent Citations
Production technology of zircon-alumina composite ceramic bead
CN101921101A
Ultra-fine grinding medium for iron oxide red powder
CN104004497A
Silicane coupling agent surface grafted modified clay as well as preparation method and use thereof
CN101254924A
Filler supporting body for industrial tower and preparation method thereof
CN102030520A